Through science, emotions and consciousness: A short journey along the history of empathy (Balthazar, 2023)
"Through science, emotions and consciousness: a short journey along the history of empathy" by Tiziana Plebani.
Keywords: science; conscience; neurosciences; emotions; reading; novel